Assessment of the prognostic value of serum beta-2 microglobulin and transforming growth factor beta levels for multiple myeloma patients - Joudah, Muthanna Mohammed; Maaroof, Raoof J. A.; Al-Rikabi, Eman H.; Makki Al-Hindy, Hayder Abdul-Amir; Mousa, Mazin Jaafar; Ramadan, Ghazi Mohamad; Al-Anbari, Abbas Jaafar Khaleel (Pharmakeftiki, 2025)
This study has evaluated the joint prognostic utility of circulating beta-2 microglobulin (β2-microglobulin) and transforming growth factor beta (TGF-β) levels in 98 patients with multiple myeloma (MM) and 31 healthy volunteers (controls). Participants were recruited from the Haematology Department of the Marjan Medical Hospital, Babil Province, Iraq, between March 2021 and December 2022. The combined biomarker model yielded an overall diagnostic accuracy of 0.862, with a sensitivity of 93.2% and specificity of 90.1% for distinguishing MM cases from healthy individuals. Notably, β2-microglobulin alone achieved an area under the curve (AUC) of 0.961 in differentiating stage III from stage II MM. These findings support the potential of integrated β2-microglobulin and TGF-β profiling to enhance diagnostic and staging precision in MM, warranting further investigation into their clinical and translational applicability.